Impedance Analysis and Optimization of Self-Powered Interface Circuit for Wireless Sensor Nodes Application - Yuan Dong; Dezhi Li; Benjamin Ducharne; Xiaohui Wang; Jun Gao; Bin Zhang (Shock and Vibration)
Energy harvesting for self-powered wireless sensor networks (WSNs) is increasingly needed. In this paper, a self-powered WSN node scenario is proposed and realized by coupling the electric charge extraction interface circuit, power management module, and wireless communication module. Firstly, the output power of an optimized self-powered energy extraction circuit is compared with different energy extraction circuits under various loads and excitation amplitudes theoretically. Then, an energy-harvesting setup is established to validate the load-carrying capacity and working condition of the self-powered optimized synchronized switch harvesting on inductor (SP-OSSHI) circuit. It gives guidance to select and estimate the appropriate energy-consuming level for the sensor and modules. Finally, by connecting the energy-harvesting system, power management element, and sensing part together, a self-powered wireless sensor node is accomplished. Under 18 Hz resonant excitation, the whole self-powered system transmits 32 bytes of data every 30 seconds including the acceleration and environment temperature. This prototype strongly proves the feasibility of the self-powered WSN node. These research results have potential to be used in different application fields.